The negative effects on mental health of being in a non-desired occupation in an increasingly precarious labour market. (December 2017) - Canivet, Catarina; Aronsson, Gunnar; Bernhard-Oettel, Claudia; Leineweber, Constanze; Moghaddassi, Mahnaz; Stengård, Johanna; Westerlund, Hugo; Östergren, Per-Olof
Abstract: Precarious employment has been associated with poor mental health. Moreover, increasing labour market precariousness may cause individuals to feel 'locked-in', in non-desired workplaces or occupations, out of fear of not finding a new employment. This could be experienced as a 'loss of control', with similar negative health consequences. It is plausible that the extent to which being in a non-desired occupation (NDO) or being in precarious employment (PE) has a negative impact on mental health differs according to age group. We tested this hypothesis using data from 2331 persons, 18–34, 35–44, and 45–54 years old, who answered questionnaires in 1999/2000, 2005, and 2010. Incidence rate ratios (IRR) were calculated for poor mental health (GHQ-12) in 2010, after exposure to NDO and PE in 1999/2000 or 2005. NDO and PE were more common in the youngest age group, and they were both associated with poor mental health. In the middle age group the impact of NDO was null, while in contrast the IRR for PE was 1.7 (95% CI: 1.3–2.3) after full adjustment. The pattern was completely the opposite in the oldest age group (adjusted IRR for NDO 1.6 (1.1–2.4) and for PE 0.9 (0.6–1.4)). The population attributable fraction of poor mental health was 14.2% and 11.6%, respectively, for NDO in the youngest and oldest age group, and 17.2% for PE in the middle age group. While the consequences of PE have been widely discussed, those of NDO have not received attention. Interventions aimed at adapting work situations for older individuals and facilitating conditions of job change in such a way as to avoid risking unemployment or precarious employment situations may lead to improved mental health in this age group. Highlights: Labour market factors influenced mental health after 5–10 years. The impact varied by age group. Young persons were more often in precarious employment & in non-desired occupations. Precarious employment had the strongest negative impact on mental health in middle age. In late working life, non-desired occupation was associated with poor mental health.